Nestedness patterns of sand fly (Diptera: Psychodidae) species in a neotropical semi-arid environment - Chaves, Luis Fernando (2016)
A common pattern in neotropical Leishmania spp. transmission is the co-occurrence of several sand fly (SF) species at endemic foci. We collected 13 SF spp. by direct aspiration in natural resting places (NRP) and 10 SF spp. with Shannon traps (ST), totaling 15 spp. with both methods, at 6 locations within a semi arid region with endemic visceral leishmaniasis transmission in Falcón State, Northwestern Venezuela. We used null modeltesting of species co-occurrence and nestedness metrics estimated with our field data to ask whether SF species composition was segregated/aggregated, and if aggregated whether there was nestedness, i.e., whether species composition across sampling locations could be described by ordered subsets of species from the most species rich location in a landscape. Results showed that SF species were aggregated (P < 0.05), i.e., most species were present in species rich locations. Similarly, SF species were significantly nested (P < 0.05). Differences in pairwise Sørensen and Simpson indices, estimated with the STdata andthe combinedST andNRPdata, werepositively associated withthedistance betweensampling locations, suggesting that species nestedness might be partially shaped by dispersal limitation. Our data showed thatthree species of medical importance were common across the sampling locations: Lutzomyia gomezi, Lutzomyia panamensis and Lutzomyia evansi, suporting that vector species do not turnover in the studied setting.